Formation of condition severity index of the industrial-building systems - Залунина, Ольга Михайловна (Technology audit and production reserves, 2016)
This article discusses the formation of the index, which reflects the financial feasibility of investing funds in the building projects. The main aim of the study is improving efficiency of the strategic plans for the development of the building sector in Ukraine by the research of algorithm to optimize the building industry management. In this paper the author suggested the formation of condition severity index of the building sector. Indexes characterizing the condition of the building system are used as the vector components. Two approaches are considered. In the first approach, it is established assessment of the severity (crisis) condition by experienced professionals and the selection of the weighting coefficients of the scalar function is carried out in accordance with the selected point scale. In the second approach, variation of severity index is approximated by time based on model representations about the mechanism of the investigated process and the selection of coefficients is carried out in accordance with the selected model. The results of their quantitative comparison are given. The author’s approach to the index formation allows coordinating investment in the building projects. The feasibility of the proposed severity index is favorable to the decision-making stage of planning to invest in the building projects. The author’s crisis intensity index allows determining the range of management and production changes that would lead to a reduction in costs.